A review of the subgenus Cladoconnus Reitter of the genus Euconnus Thomson (Coleoptera: Staphylinidae: Scydmaeninae) from the Balkan Peninsula, Turkey and Caucasus - Hlaváč, Peter (Zootaxa, 2013)
The subgenus Cladoconnus Reitter, 1909 of the megadiverse genus Euconnus Thomson, 1859 is redescribed and revised for the Balkan Peninsula, Turkey and Caucasus. The following species are described: Euconnus (Cladoconnus) gagrani-cus sp. nov., E. (C.) ispartaensis sp. nov., E. (C.) meybohmi sp. nov., E. (C.) brachati sp. nov. and E. (C.) croaticus sp. nov. Lectotypes are designated for E. (C.) anatolicus Franz, 1997, E. (C.) dodecanicus Franz, 1966, E. (C.) robustus Reit-ter, 1882 and E. (C.) winneguthi Apfelbeck, 1907. Euconnus (Cladoconnus) major (Motschulsky, 1851) is placed as a ju-nior synonym of E. (C.) motschulskii (Motschulsky, 1837). Two species groups, schlosseri and denticornis are defined; identification keys to the groups and species are given.